2018
DOI: 10.1002/ccr3.1596
|View full text |Cite
|
Sign up to set email alerts
|

Mild phenotypes associated with an unbalanced X‐autosome translocation, 46,X,der(X)t(X;8)(q28;q13)

Abstract: Key Clinical MessageUnbalanced X‐autosome translocation can result in various phenotypic manifestations. We present the first case of 46,X,der(X)t(X;8)(q28;q13) in a 34‐year‐old female with relatively mild manifestations, including congenital heart disease, epicanthal fold, mild intellectual disability, and menstrual irregularity. Our findings expand the known spectrum of unbalanced X‐autosome translocations, for improved clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…The use of more than one polymorphic locus to determine the XCI offered an advantage in overtaking the PCR artifacts that are inherent to the techniques (Bertelsen et al, 2011), as for the ZDHHC15 gene assay in our patient 2, allowing us to determine a heavily skewed inactivation for all the patients. By performing a late‐replication analysis using the incorporation of EdU, we showed that the heavily skewed XCI pattern occurred toward the derivative chromosome for all the patients (Table 1, Figure 1), as it was expected from previous reports of similar cases (Stankiewicz et al, 2006; Watanabe et al, 2018; Yatsenko et al, 2004; Yeung et al, 2014) and from their severe clinical picture.…”
Section: Discussionsupporting
confidence: 82%
“…The use of more than one polymorphic locus to determine the XCI offered an advantage in overtaking the PCR artifacts that are inherent to the techniques (Bertelsen et al, 2011), as for the ZDHHC15 gene assay in our patient 2, allowing us to determine a heavily skewed inactivation for all the patients. By performing a late‐replication analysis using the incorporation of EdU, we showed that the heavily skewed XCI pattern occurred toward the derivative chromosome for all the patients (Table 1, Figure 1), as it was expected from previous reports of similar cases (Stankiewicz et al, 2006; Watanabe et al, 2018; Yatsenko et al, 2004; Yeung et al, 2014) and from their severe clinical picture.…”
Section: Discussionsupporting
confidence: 82%
“…Although Asian eyes do not much differ in some other recorded features (eg, length and ellipticity), the presence of an epicanthal fold (a skin fold of the upper eyelid) is viewed as a unique Asian hallmark (the so‐called “slanted” eyes). This skin fold, found associated with a X‐autosomal translocation, is however present at a much lower frequency in some other ethnicities such as Africans and Europeans . Taking this phenotype as a unique and specific Asian trait is therefore questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, black/brown iris (eumelanin‐based) largely predominate, worldwide . Although the presence of an epicanthal fold in Asian subjects (the so‐called “slanted eyes”), linked to an X‐autosomal translocation is a common but variable trait, the latter can also be observed in other ethnicities, although at a lesser frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The spread of X-inactivation into the autosomal regions could affect the phenotype, which could lead to a more severe or a mild clinical presentation depending on the patient's chromosomal constitution. Watanabe et al reported a 34 years old female with mild phenotypes including congenital heart disease, epicanthal fold, mild intellectual disability, and menstrual irregularity associated with an unbalanced X-autosome translocation, 46,X,der(X)t(X;8)(q28;q13), and suspected that the patient had mild phenotypes due to the inactivation of the abnormal X chromosome 8q13-qter and the presence of a small deletion of Xq28-qter [ 19 ].…”
Section: Discussionmentioning
confidence: 99%